Triploidia 69, XXY u zivorodeného dietata - Pasková, K; Braxatorisová, T; Geislerová, V; Sramková, K; Martanovic, P; Pagácová, E; Duríková, M (Ceskoslovenska patologie, 1992)
Triploidy 69, XXY was described in a liveborn foetus weighing 760 g. Diagnosis was based on postmortal cytogenetical analysis.
Keywords: Sex Chromosome Aberrations; novorozenec; karyotypizace; Infant, Newborn; aberace pohlavních chromozomů; Humans; mužské pohlaví; polyploidie; lidé; Male; Polyploidy; Karyotyping